Makna Fungsi Pañcatathāgata di Candi Bubrah - Waluyo, Waluyo; Yasa, I Wayan Suka; Wirawan, I Gusti Bagus (JANUS, 2023)
The pañcatathāgata statues at Candi Bubrah are functionally valuable in the large structure of the temple as a maṇḍala. The symbolic and semiotic dimensions of the pañcatathāgata archaelogical artifact at Candi Bubrah, which represent the objects of meditation in the stages of achieving Buddhahood, need to be studied. This research aims to describe the doctrinal reasons behind the presence of the pañcatathāgata in Candi Bubrah; analyze their function in meditation practices; and explain the significance of these function for the achievement of Liberation. Peirce’s trichotomy relations analysis and Strauss’s structuralism approach with qualitative methods are used to examine the material objects of this study. The pañcatathāgata at Candi Bubrah serves as a guide in practicing Buddhist meditation. The meditative functions of the pañcatathāgata statues, each with its own characteristics, as objects of meditation for the development of tranquility, are as follows: Akṣobhya, representing the bhūśparsa mudra, the east, the blue element, the vajra symbol, the physical element, rejection, mirror-like knowledge; Ratnasambhava, with the varada mudra, the south, the yellow element, the jewel, perception, arrogance, knowledge of equality; Amitābha, reflected by the samādhi mudra, the west, the red element, the lotus, the forms of the mind, greed, knowledge of differentiation; Amoghasiddhi, with the characteristic of the abhaya mudra, the north, the green element, the viśvavajra, the knower, jealousy, knowledge of attainment; and Vairocana, with the dharmacakra mudra, the center, the white element, the wheel, feelings, misunderstanding, knowledge of what is. The meditative functions of the pañcatathāgata statues, which represent mental qualities, significantly lead someone to Liberation.